Eat, pray bird - Huang, Ji (2016)
Came a long way since pre-production class. Ideas got scratched many times, we started with a gag film about how lion dance became to be, set in ancient china, the emperor asks for a competition for the best entertainer and the lion dancers are the ones who got selected and be passed down from generations to generations. Next, we went with a forest hermit finding companionship with a lost traveler and then we went for dwarves mining rocks, but the twist is the rocks seep out wine instead of gems, and wine is their currency.